Effect of three different drinks on physical variables in male athletes, during a running trial - Umaña Alvarado, Mónica (2006)
Purpose: Determine the effects of different drinks on physical variables in male athletes. Methods: In a double-blind, crossover randomized design, 13 runners (mean age = 25.54 ± 6.75 yrs old) completed three, one hour running trial on a treadmill under stressful conditions (mean temperature = 30 °C, mean relative humidity = 60%). Tests were performed on 3 separate (1 week apart) occasions. During the trials, subjects drank their desired amount of either 6% carbohydrate sports drink (SD), 11% carbohydrate energy drink (ED) or placebo beverage (PL) every 15 minutes. Variables were total distance, rating of perceived effort (RPE), palatability, sensation of fullness, gastrointestinal (GI) symptoms, percent dehydration and sweat rate. The study considered a co-variable, the total intake of each drink during the tests. Statistical analysis using SPSS 8.0 and SAS included descriptive statistics, analysis of variance, multi-analysis of co-variance and McNemar χ2 test. Results: There was no significant difference involuntary mean intake during the trials (SD = 987.46 ± 299.00 ml; ED = 782.46 ± 274.30 ml; PL = 786.54 ± 212.36 ml) (p = .055). No difference in mean total distance was found between the drinks (SD = 11.72 ± 1.21 km; ED = 11.49 ± 1.26 km; PL = 11.38 ± 1.42 km) (p = .34). There was no difference in RPE or any other variable during the trials, including palatability (SD = 7.33 ± 0.82, ED 6.00 ± 1.88, PL = 5.81 ± 1.64) (p = .077). More subjects reported GI problems when drinking ED or PL (92%) compared to SD (62%). No significant association was found between the type of drink and GI symptoms during the tests (p = .131). Conclusions: Performance in one hour running trial under stressful conditions was the same when consuming any drink. Subjects perceived the same effort, palatability and sensation of fullness when drinking SD, ED or PL. No association between type of drink and GI problems was found, but a high percentage of subjects reported this problem (ED and PL = 92%; SD = 62%).